Model Pembelajaran PAI di Sekolah Menengah Kejuruan (SMK) Negeri 1 LAIS - Zulhijra, Zulhijra; Malik Nurrohim (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to find a model overview on Islamic Religious Education (PAI) at the SMKN 1 Lais school in Musi district of Banyuasin, southern Sumatra. In this study, the researchers used qualitative approaches and data collection techniques used are Observation and interview techniques that target teachers of Islamic Religious Education (PAI) and other teachers as well as the head of school as the main benchmark as informants or data sources in order to obtain concrete data. After the data is collected the next step is to analyze the data obtained, in this case the researchers use the Miles dkk approach i.e., data selection and data placement, data presentation, data perivication and conclusion. In this study found the following conclusion: the learning model used by the teacher of Islamic Religious Education (PAI) in the school SMKN 1 Lais is a model of live learning and Experiential Learning, that is learning that utilizes the emotions and experiences of the pupils, is a learning model that brings pupils understand learning with the experience experienced by pupils creates pupils become creative, not only listening theory, but pupils also perform meaningful activities that create self-confidence and increase adrenaline so that pupils can find the relationship between knowledge and what they have with its implementation in their lives both in the family environment and in the community environment.